IDENTIFICATION OF NOVEL TL 15 PEPTIDE TARGET IN PORPHYROMONAS GINGIVITIS AND PROPOSING INHIBITOR AGAINST HEME-BINDING - Thiru Kumaran V, Dr Sanyukta Singh (Cuestiones de Fisioterapia, 2023)
This study focuses on the identification of a novel TL 15 peptide target in Porphyromonas gingivalis, exploring its potential as a therapeutic target against heme-binding. The aim is to propose an inhibitor that could disrupt this interaction